2015 IEEE International Conference on Computer Vision (ICCV) 2015
DOI: 10.1109/iccv.2015.97
|View full text |Cite
|
Sign up to set email alerts
|

Point Triangulation through Polyhedron Collapse Using the l∞ Norm

Abstract: Multi-camera triangulation of feature points based on a minimisation of the overall 2 reprojection error can get stuck in suboptimal local minima or require slow global optimisation. For this reason, researchers have proposed optimising the ∞ norm of the 2 single view reprojection errors, which avoids the problem of local minima entirely. In this paper we present a novel method for ∞ triangulation that minimizes the ∞ norm of the ∞ reprojection errors: this apparently small difference leads to a much faster bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…However, more recent works used the L ∞ norm in both aspects. The polyhedron collapse method proposed by Donne et al used the L ∞ norm in both the reprojection error and the aggregation error [18]. Its process only involves unary quadratic equations and some basic algebraic geometry, which is very simple and fast.…”
Section: L ∞ Triangulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more recent works used the L ∞ norm in both aspects. The polyhedron collapse method proposed by Donne et al used the L ∞ norm in both the reprojection error and the aggregation error [18]. Its process only involves unary quadratic equations and some basic algebraic geometry, which is very simple and fast.…”
Section: L ∞ Triangulation Methodsmentioning
confidence: 99%
“…It shows that L ∞ optimization comes down to minimizing a cost function with a single minimum (local or global) on a convex domain [17]. Donné et al [18] proposed the Polyhedron collapse method based on the L ∞ norm. It adopts the L ∞ norm to quantify both the single view reprojection error and the aggregated reprojection error, and it is simpler and faster than previous methods [19], [20].…”
Section: Introductionmentioning
confidence: 99%
“…For p = 1, the Dinkelbach method was used as the embedded solver for Algorithm 1. For p = ∞, the state-of-the-art polyhedron collapsed method [13] was used as the embedded solver. Evidently the results show that the coreset method is able to significantly speed up global convergence.…”
Section: Extensions To 1 and ∞ Reprojection Errormentioning
confidence: 99%
“…Unlike the sum of squared error function which contains multiple local minima, the maximum reprojection error function is quasiconvex and thus contains a single global minimum. Algorithms that take advantage of this property have been developed to solve such quasiconvex problems exactly [6], [7], [8], [9], [10], [11], [12], [13]. In particular, Agarwal et al [10] showed that some of the most effective algorithms belong to the class of generalised fractional programming (GFP) methods [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by these difficulties, the ℓ ∞ -norm has recently been considered as a measure of the reprojection error [3], [4], [17]. Although this may not correspond to the best model of the underlying uncertainty, the resulting cost is a quasi-convex function and efficient algorithms can find the global optimum [5]. However, since the ℓ ∞norm implicitly assumes a bounded noise model, care must be taken to limit the potential catastrophic effect of outliers [18], [19].…”
Section: Introductionmentioning
confidence: 99%